Two novel variants in CNNM2 disrupts magnesium efflux leading to neurodevelopmental disorders - Li, Huijuan; Liu, Jing; Liu, Yingdi; Liu, Yaning; Lu, Kehui; Wen, Juan; Zhu, Huimin; Liang, Desheng; Li, Zhuo; Wu, Lingqian (Frontiers in Genetics, 2025)
BackgroundHypomagnesemia, seizures, and impaired intellectual development 1 (HOMGSMR1) is a rare neurodevelopmental disorder associated with magnesium homeostasis disruption, caused by mutations in the CNNM2 gene. HOMGSMR1 demonstrates considerable clinical heterogeneity, but the genotype-phenotype relationship remains insufficient.MethodsWe recruited two unrelated families with NDDs, and potential variants were identified through whole exome sequencing and confirmed by Sanger sequencing. Quantitative PCR, Western blotting, immunofluorescent staining, and flow cytometry were used to assess functional changes in candidate CNNM2 variants.ResultsTwo novel variants, p.E298del and p.P360R, in CNNM2 gene were identified. The unique facial features of proband 1 may broaden the known phenotypic spectrum of HOMGSMR1. Functional studies confirmed that the p.E298del and p.P360R variants increased CNNM2 transcription and protein levels, impairing the proper localization of the CNNM2 protein to the cell membrane. Two variant proteins accumulated in the cytoplasm and formed clumps. Furthermore, intracellular Mg2+ levels were higher in cells with these variants, disrupting magnesium homeostasis and potentially contributing to hypomagnesemia. Notably, the proteins of these two variants exhibited reduced stability and were prone to degradation, potentially providing new insights into the pathogenic mechanisms of CNNM2.ConclusionOur study expands the mutation and phenotypic spectrum, as well as the functional studies of CNNM2, and contributes to genetic testing and prenatal diagnosis in families with HOMGSMR1.